1997
DOI: 10.1159/000196720
|View full text |Cite
|
Sign up to set email alerts
|

High Altitude Pulmonary Edema

Abstract: Altitude, speed and mode of ascent and, above all, individual susceptibility are the most important determinants for the occurrence of high-altitude pulmonary edema (HAPE). This illness usually occurs only 2-5 days after acute exposure to altitudes above 2,500-3,000 m. Chest radiographs and CT scans show a patchy predominantly peripheral distribution of edema. Wedge pressure is normal at rest, and there is an excessive rise in pulmonary artery pressure (Ppa) which precedes edema formation. Bronchoalveolar lava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 14 publications
1
45
0
3
Order By: Relevance
“…An abnormal rise of pulmonary artery pressure plays a crucial role in the pathophysiology of HAPE (Bärtsch, 1997;Bärtsch, 1999). Studies using right-heart catheterization have demonstrated that HAPE-susceptible subjects have an abnormal rise in pulmonary artery pressure during brief exposure to hypoxia (FIO 2 5 0.12) at low altitude (Hultgren, Grover, and Hartley, 1971;Eldridge et al, 1996), and also during exercise in normoxia (Eldridge et al, 1996;Kawashima et al, 1989).…”
Section: Noninvasive Assessment Of Pulmonary Artery Pressurementioning
confidence: 99%
“…An abnormal rise of pulmonary artery pressure plays a crucial role in the pathophysiology of HAPE (Bärtsch, 1997;Bärtsch, 1999). Studies using right-heart catheterization have demonstrated that HAPE-susceptible subjects have an abnormal rise in pulmonary artery pressure during brief exposure to hypoxia (FIO 2 5 0.12) at low altitude (Hultgren, Grover, and Hartley, 1971;Eldridge et al, 1996), and also during exercise in normoxia (Eldridge et al, 1996;Kawashima et al, 1989).…”
Section: Noninvasive Assessment Of Pulmonary Artery Pressurementioning
confidence: 99%
“…This condition normally occurs at altitudes above 3000 m and affects many people including previously fit individuals. [1][2][3][4] Advances in the understanding of the biochemical pathways involved in the physiologic response to hypoxia have led to greater insights into the pathogenesis of HAPE.…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews are available to trace that history (Schoene, 1987;Hackett and Roach, 1990;Richalet, 1995;Bartsch, 1997). Pioneered by Hultgren, studies in the 1960s and 1970s focused on pulmonary and cardiac hemodynamics to determine if there was left ventricular dysfunction and/or excessive pulmonary hypertension that led to a breakdown in the pulmonary vascular barrier, resulting in diffuse pulmonary edema and hypoxemia.…”
Section: Schoenementioning
confidence: 99%